On classification of associative non-division genetic algebras - Ganikhodjaev, Nasir; Dustmuradova, Gavhar (American Institute of Physics, 2013)
In general, the algebras which arise in genetics are non-division algebra. In this paper we describe genetic significance of non-invertible elements, present a construction of non-division genetic algebras, and investigate the problem of their classification.